Digital Transformation in Public Administration: Its Impact on Government Service Effectiveness - Desita Rahayu; Sri Suharti; Ridianto Ridianto; Romdana Romdana; Muhammad Solihin (Lembaga Bale Literasi, 2025)
Digital transformation has become an important component of modern public administration as governments seek to improve the effectiveness, efficiency, accessibility, and responsiveness of public services. The adoption of digital technologies enables government institutions to simplify administrative processes, reduce service delivery time, improve information accessibility, and strengthen coordination between public institutions and citizens. This study aims to examine the impact of digital transformation on government service effectiveness. The study employs a quantitative approach using a survey method. Data were collected from public service users and analyzed using descriptive and inferential statistical techniques. Digital transformation was measured through several dimensions, including digital infrastructure, accessibility of digital services, integration of information systems, digital employee competence, and the utilization of technology in service delivery. Government service effectiveness was assessed based on service quality, efficiency, timeliness, accessibility, responsiveness, and achievement of service objectives. The findings indicate that digital transformation has a positive and significant impact on government service effectiveness. The implementation of digital systems facilitates faster service delivery, improves access to government information and services, reduces administrative procedures, and supports more responsive interactions between government institutions and citizens. However, the effectiveness of digital transformation also depends on adequate infrastructure, employee competence, system integration, data security, and citizens' digital literacy. The study concludes that digital transformation can serve as an important strategy for improving government service effectiveness when supported by appropriate institutional capacity and sustainable digital governance. The findings provide practical implications for public administrators in designing citizen-oriented digital services and strengthening the capacity of government institutions to respond to the demands of the digital era.